2014
DOI: 10.1103/physrevd.90.055006
|View full text |Cite
|
Sign up to set email alerts
|

Electron electric dipole moment as a sensitive probe of PeV scale physics

Abstract: We give a quantitative analysis of the electric dipole moments as a probe of high scale physics.We focus on the electric dipole moment of the electron since the limit on it is the most stringent.Further, theoretical computations of it are free of QCD uncertainties. The analysis presented here first explores the probe of high scales via electron electric dipole moment (EDM) within MSSM where the contributions to the EDM arise from the chargino and the neutralino exchanges in loops.Here it is shown that the elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Thus in this case all the mixing parameters, given in Eq. (13), are set to zero. The second analysis is for the MSSM extension where the mixings of the vectorlike generation with the three generations are switched on.…”
Section: The Analysis Of Electric Dipole Moment Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Thus in this case all the mixing parameters, given in Eq. (13), are set to zero. The second analysis is for the MSSM extension where the mixings of the vectorlike generation with the three generations are switched on.…”
Section: The Analysis Of Electric Dipole Moment Operatormentioning
confidence: 99%
“…In view of this one could turn the indication of a large SUSY scale as a possible resolution of the EDM problem of supersymmetric models. In fact it has been suggested recently [10,11,12,13,14], that one can go further and utilize the current and future improved data on the EDM limits to probe mass scales far beyond those that may be accessible at colliders. We also note in passing that a large SUSY scale also helps suppress flavor changing neutral currents (FCNC) in supersymmetric models and helps stabilize the proton against rapid decay from baryon and lepton number violating dimension five operators in grand unified theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include a fine tuning of the phases to be small [24], suppression of the EDM by large sparticle masses [25], suppression of the EDM where various contributions conspire to cancel, i.e., the cancellation mechanism [26,27] as well as other possible remedies (see, e.g., [28]). It has also been suggested that the EDM be used as a probe of new physics beyond the standard model [29,30,31,18,32]. Specifically the experimental limits on the EDMs can be used as vehicles to probe a new physics regime not accessible otherwise to current and future detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Further, vectorlike multiplets arise in a variety of settings such as in grand unified models and in string and D brane models [8,10,11]. Vectorlike generations have been considered by several authors since their discovery would constitute new physics (see, e.g., [9,10,11,12,13,14,15,16,17,18,19,20,21,22]). Such models have new sources of CP violation and thus can generate substantial size dipole operators.…”
Section: Introductionmentioning
confidence: 99%